Relationship of environmental factors with smoking behavior in students - Aristi, Maria Aviani; Hastuti, Agustina Sri Oktri; Nugraha, Dwi Antara (International Journal of Health Science and Technology, 2024)
According to the World Health Organization (WHO), in 2020, the number of smokers worldwide was 991 million people. The Western Pacific has the highest number of smokers over 15, 377 million in 2020. South Asia is in second place, followed by Europe. In Indonesian students aged 13 to 15, two out of every three boys and one out of every five girls have tried tobacco products. This study aimed to identify the characteristics of respondents, environmental factors, and smoking behavior and analyze the relationship between environmental factors and smoking behavior in students. This study used correlational descriptive with a cross-sectional approach. Held in STIKes Panti Rapih Yogyakarta. The sample size used a total sampling technique with 73 samples. The result shows that most of the smoker respondents were aged ≥20 years (42.5%), had a positive environment (63.14%), and had moderate smoking behavior (64.4%). Bivariate analysis used the Spearman test with a sig (ρ value) of 0.000 (< α 0.05). There is a relationship between environmental factors and smoking behavior. Suggestions for smokers to reduce bad smoking habits, for institutions to provide guidance and re-explain the rules in student ethics books on smoking prohibition, and for future researchers to examine one of the factors that most influence smoking behavior